NM Auto Shop Marketing Strategy: An Analysis of Service Quality and Price Fairness in Building Customer Loyalty - Eric Anthonio; Metta Padmalia; Yuli Kartika Dewi (Green Publisher Indonesia, 2026)
This research aims to analyze the influence of Service Quality and Price Fairness on Customer Loyalty through a dual mediation model involving Customer Satisfaction and Customer Trust, while comparing the effectiveness of transactional learning and relational learning pathways in building loyalty within an independent workshop context. A quantitative explanatory cross-sectional design was employed. Data were collected from customers who had visited Bengkel NM at least twice within the preceding eighteen months using purposive sampling, and were analyzed through Partial Least Squares Structural Equation Modeling. The findings reveal that Service Quality has a positive and significant direct effect on Customer Satisfaction, Customer Trust, and Customer Loyalty, while Price Fairness is only proven to significantly influence Customer Trust. The direct effect of Price Fairness on Customer Loyalty was not significant. Although all four specific mediation paths were individually non-significant, Service Quality was proven to operate through aggregate mediation, categorized as complementary partial mediation, whereas Price Fairness demonstrated a non-mediation pattern. The novelty of this research lies in testing a dual mediation model that simultaneously compares satisfaction and trust pathways within the context of an Indonesian independent workshop with premium pricing characteristics. The findings indicate an evaluative fusion phenomenon between Customer Satisfaction and Customer Trust, suggesting that in services characterized by high technical information asymmetry, customers tend to merge satisfaction and trust evaluations into a single holistic assessment, rendering the independence of both pathways unverifiable through cross-sectional design.